Forensic facial identification – reconstruction of facial geometry and shape from dental dimensions - Chitara, Nandini; Krishan, Kewal (Anthropological Review, 2024)
Human identification has always remained as a main task of forensic anthropology and forensic science for various purposes. The purpose of human identification may vary from legal identity to disaster victim identification, from criminal identity to unidentified deceased identification. The condition, such as putrefaction, charring and mutilation of corpse always become an obstacle during the process of identification. Due to surviving nature of teeth, they may serve as evidence for identification in highly decomposed conditions. Therefore, a cross-sectional study was conducted on 207 participants (93 males and 114 females) in the age range of 21 to 45 years with the aim of two-dimensional facial reconstruction. Dental casts, anthropometric facial measurements and facial photographs were obtained from the participants. Dental measurements were taken on the cast in the laboratory. Statistical analysis revealed a weak but statistically significant correlation between the dental and facial parameters. The geometrical faces and the shapes were reconstructed based on the dental dimensions. The reconstructed facial geometry and shapes were very similar to the true facial geometry and facial shapes of the individual. By improving identification of disaster victims and unidentified deceased, the results of the study can have considerable implications in forensic and medico-legal case-works.